Private Participation in Infrastructure in Developing Countries : Trends, Impacts, and Policy Lessons - Harris, Clive (Washington, DC: World Bank, 2013)
Governments have long recognized the vital role that modern infrastructure services play in economic growth and poverty alleviation. For much of the post-Second World War period, most governments entrusted delivery of these services to state-owned monopolies. But in many developing countries, the results were disappointing. Public sector monopolies were plagued by inefficiency. Many were strapped for resources because governments succumbed to populist pressures to hold prices below costs. Fiscal pressures, and the success of the pioneers of the privatization of infrastructure services, provided governments with a new paradigm. Many governments sought to involve the private sector in the provision and financing of infrastructure services. The shift to the private provision that occurred during the 1990s was much more rapid and widespread than had been anticipated at the start of the decade. By 2001, developing countries had seen over $755 billion of investment flows in nearly 2500 infrastructure projects. However, these flows peaked in 1997, and have fallen more or less steadily ever since. These declines have been accompanied by high profile cancellations or renegotiations of some projects, a reduction in investor appetite for these activities and, in some parts of the world, a shift in public opinion against the private provision of infrastructure services. The current sense of disillusionment stands in stark contrast to what should in retrospect be surprise at the spectacular growth of private infrastructure during the 1990s.